Paying for crime: frauds in DPVAT insurance and their impacts on society - Beatriz Peres Lopes; João Vinícius França Carvalho (BBR: Brazilian Business Review)
The goal of this paper is to assess the weight of fraudulent claim payments of DPVAT insurance by the insurer Líder, a consortium of private insurers who manage this product. Using the Actuarial Credibility Theory, and a official database, the discrepancy between the DPVAT claims ratio and the claims ratios of other private automobile insurance lines of business, proxies for the ideal premium formation for having better system of frauds detection and prevention. The results indicate significant differences among the values. Additionally, in two counterfactual scenarios, it was estimated: (i) what would be the value of the DPVAT premium in case the fraud effects were purged, aiming to analyze whether the verified heterogeneity could be explained by the volume of proven frauds; (ii) the financial volume that could potentially be saved by society in case the frauds were subtracted since 2006. It is possible to affirm that not only would the DPVAT’s claims ratio be reduced, but also the premiums paid by the insured. Finally, the estimates suggest that society could have saved over BRL 15 billion in 14 years.